Knowledge-based development dynamics in less favoured regions: insights from Australian and Icelandic university towns - Tan Yigitcanlar; Ingi Runar Edvardsson; Hjalti Johannesson; Md Kamruzzaman; Giuseppe Ioppolo; Surabhi Pancholi (2017)
Knowledge-based development (KBD) is a widely practiced policy and is signified as an effective development approach particularly for the metropolitan city-region context. Even though, increasing recognition of this policy resulted in some initiatives in less favoured regions – such as regional university towns – its appropriateness for this context has not been investigated adequately. This paper explores the concept thoroughly in regional university town settings from the lens of the triple-helix model – a critical element for success in KBD. The study aims to broaden our understanding on the challenges of implementing a successful triple-helix model in regional university towns by providing evidence from different country contexts – Australia and Iceland. The methodology of the comparative case investigation incorporates policy and stakeholder perception analyses. Results reveal the journey of the investigated cases, their limited accomplishments and failure factors. Findings shed light on the developmental challenges of regional university towns by highlighting critical issues relating to suitability, appropriate implementation and effectiveness of the KBD policy.